The evaluation and design of a short depression screening tool in Turkish older adults. (21st March 2018) - Dokuzlar, Ozge; Soysal, Pinar; Usarel, Cansu; Isik, Ahmet Turan
ABSTRACT: Introduction: Depression is a common and serious healthcare problem for older adults. This study aimed to determine the validity and reliability of GDS-4 and GDS-5 in Turkish, and to establish a new short-form Geriatric Depression Scale (GDS) for our population, and also determine the superiority of each short scale to another. Methods: A total of 437 outpatients were enrolled in the study. A researcher evaluated all participants according to the Diagnostic and Statistical Manual of Mental Disorders-fifth edition (DSM-5) diagnostic criteria, and then another researcher applied GDS-15 to all participants. We obtained the answers of short GDS forms, examined in this study, from GDS-15 forms. After Cohen's κ analysis, we compared the diagnostic value of each question for geriatric depression according to their κ values, and developed three (TGDS-3), four (TGDS-4), five (TGDS-5), and six (TGDS-6) question scales to screen geriatric depression in Turkish population. Results: A total of 437 participants were assessed. The mean age (SD) of the patients was 72.95 years (7.37).Cronbach's α values of GDS-4 and GDS-5 were <0.70. Cronbach's α values of TGDS-3, TGDS-4, TGDS-5, and TGDS-6 were >0.70. The best cut-off values were ≥5 for GDS-15 and GDS-5, and ≥1 for others. Discussion: GDS-15 is the most powerful screening scale for geriatric depression. GDS-4 and GDS-5 are not eligible for depression screening in Turkish older adults. All new short scales are valid and reliable, and TGDS-4 is a practical, less time-consuming option for daily practice.